Sintering of systems with interacting components - Savit͡skiĭ, A. P. (Materials science foundations, 2009)
The aim of this publication is to acquaint those readers who are interested in the fundamentals of powder materials sintering, with the latest scientific achievements which are important to its successful practice. The book contains new information, not previously known in the West, as well as offering a totally fresh view of this vital issue. The work discloses to western eyes a new scientific trend in the science of sintering systems with interacting components; a trend of which many experts are unaware. The new approach will considerably enrich and advance investigations into the theory and.